Impact of post appendectomy pain - Lamture, Yashwant R.; Gajbhiye, Varsha P.; Shinde, R. K.; Kiran, Kher (International Surgery Journal, 2017)
Background: Appendectomy is one of the commonest abdominal operation performed during emergency hours for acute appendicitis. Acute appendicitis is the common pathology in right lower abdomen. Postoperative complications following appendicectomies are not uncommon and reflect the degree of peritonitis that was present at the time of operation. Intra operative spillage and intercurrent diseases that may predispose to the complication. But all patients are not relieved of their symptoms following surgery. Few patients continue to visit surgical OPD for continuous pain in right iliac fossa even after appendectomy had been performed. So, we design proforma to find out exact cause of pain. This study is a sincere effort on our part to solve secrets of post appendectomy pain. Methods: Evaluation of patient who continue to visit even after removal of appendix for pain in right iliac fossa. It was tried to establish correlation between relief of pain and histopathology report of appendix to justify the appendicectomies. These patients investigated to find out underlying organic cause. Functional patients were subjected for psychological evaluation. Results: In present study from June 2006 to August 2008 we enrolled around 30 patients with complaints of pain in right iliac fossa even after appendectomy. 60% were female and 40% were male in a present study. Out of 30 cases 24 patient means 80%, were in the age group of 20 to 40 years. We found one patient means 3.33% with clinical diagnosis of stump appendicitis on radiological (barium meal follows through) examination was confirmed who responded to conservative line of treatment. All patients presented with pain in right iliac fossa symptom was the criteria for selection of patients. Exception of single patient of stump appendicitis rest were having other treatable causes. Conclusions: Out of 30 patients only one patient was having actual stump appendicitis. It is not correct to say that post appendectomy pain is a complication of surgical procedure, as multiple treatable causes were found in 29 patients. Study demonstrated that most of these patients really had organic disease. Only two patients were simple victims of psychosomatic pain. This study enlightened nicely regarding various delayed complications of appendectomy.